Specific Private-Legal Aspects of the Blockchain System Functioning - Chilachava, Mariam (Journal of Law, 2021)
In the 21st century, humanity is facing a fourth - technological revolution, characterized by an amazing pace and scale of development of digital technology. The cause of this revolution is blockchain technology, one of the most relevant, discussed and promising systems today, which is also becoming the basis of the new digital economy. The goal of the work is to introduce the essence and structure of the blockchain technology to readers, to analyze the blockchain system in the private-legal context, to discuss private-legal endogenous and exogenous problems reasoned by DLT implemented transactions, to contradict the autonomy of the blockchain system with national legislation, to offer legislative alternative for legal regulation of the blockchain system, to define the necessity for symbiotic coexistence of technologies and the Law and to offer the ways for finding the compromises needed for such coexistence.